Intravitreal bevacizumab for diabetic macular oedema: 5-year results of the Pan-American Collaborative Retina Study group. Issue 12 (24th February 2016) - Arevalo, J Fernando; Lasave, Andres F; Wu, Lihteh; Acon, Dhariana; Farah, Michel E; Gallego-Pinazo, Roberto; Alezzandrini, Arturo A; Fortuna, Veronica; Quiroz-Mercado, Hugo; Salcedo-Villanueva, Guillermo; Maia, Mauricio; Serrano, Martin; et al.
Abstract : Background/aims: To report the long-term anatomical and functional outcomes of patients with centre-involved diabetic macular oedema (DME) treated with intravitreal bevacizumab (IVB). Methods: Retrospective case series. Patients diagnosed with centre-involved DME that were treated with at least one injection of 1.25 mg IVB and had a minimum follow-up of 60 months. Patients underwent measurement of best-corrected visual acuity (BCVA), ophthalmoscopy, optical coherence tomography and fluorescein angiography at baseline, 6-month, 12-month, 24-month, 36-month, 48-month and 60-month visits. The paired samples t test was used to compare the central macular thickness (CMT) and BCVA with baseline values. Statistical significance was indicated by p<0.05. Results: Two hundred and one consecutive patients (296 eyes) were included. The mean number of IVB injections per eye was 8.4±7.1 (range: 1–47 injections). At 5 years, the BCVA remained stable at 20/100 (logarithm of the minimum angle of resolution=0.7±0.4). Eighty-six (29%) eyes improved ≥2 lines of BCVA, 129 (43.6%) eyes remained stable and 81 (27.4%) eyes lost ≥2 lines of BCVA at 60 months. Mean CMT decreased from 403.5±142.2 μm at baseline to 313.7±117.7 μm over 5 years follow-up (p≤0.0001). Conclusions: The early visual gains due to IVB were not maintained 5 years after treatment.